1997
DOI: 10.1037/0735-7044.111.2.404
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sex and MK-801 on auditory-processing deficits associated with developmental microgyric lesions in rats.

Abstract: Neonatally induced microgyric lesions produce defects in rapid auditory processing in adult male rats. Given that females across species are less susceptible to the deleterious effects of neural injury and that treatment with neuroprotective agents at the time of injury can reduce neural damage, the authors tested the effects of sex and neuroprotectant exposure on the behavioral consequences of microgyric lesions in rats. Results showed that sham but not microgyric males were able to perform the task at the fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
43
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 57 publications
4
43
2
Order By: Relevance
“…Another interesting aspect uncovered in these studies is that only male rats and mice with microgyri or ectopias were initially found to have impaired auditory function [26,27]. Female rats showed normal auditory performance and did not show a similar anatomical disruption of the MGN, even though they presented with microgyri as severe as those in males [22].…”
Section: More Insights From Animal Modelsmentioning
confidence: 91%
“…Another interesting aspect uncovered in these studies is that only male rats and mice with microgyri or ectopias were initially found to have impaired auditory function [26,27]. Female rats showed normal auditory performance and did not show a similar anatomical disruption of the MGN, even though they presented with microgyri as severe as those in males [22].…”
Section: More Insights From Animal Modelsmentioning
confidence: 91%
“…Male rats with induced cortical malformation, which develop secondary changes in the thalamus, show deficits in auditory processing (Fitch, Brown, Tallal, & Rosen, 1997;Herman, Galaburda, Fitch, Carter, & Rosen, 1997). Animals showing neuronal changes in the thalamus (males) cannot process rapidly changing sound stimuli, while control males and females with malformations perform normally.…”
Section: Neuronal Migration Anomalies and Behavior: Animal Studiesmentioning
confidence: 99%
“…In the current experiment we have extended these results to include the VB nucleus. We have previously reported that male rats with induced microgyria have defects in rapid auditory processing (Fitch et al, 1994(Fitch et al, , 1997aClark et al, 2000a,b;Peiffer et al, 2001Peiffer et al, , 2003Peiffer et al, , 2004, suggesting that these changes in the thalamus have functional consequences. In the current experiment, we report that there are significantly more FJB-positive profiles in VB at 24 h in males when compared with females.…”
Section: Sexually Dimorphic Effects Of Early Injurymentioning
confidence: 99%
“…Thus, focal collections of neurons in the molecular layer can be induced by puncture wounds at or around birth (Rosen et al, 1992b), and freezing injury to the developing cortical plate induces malformations that resemble human four-layered microgyria (Dvorák and Feit, 1977;Dvorák et al, 1978;Humphreys et al, 1991;Rosen et al, 1992a;Ferrer et al, 1993;Marret et al, 1995). These induced malformations have been used to model a variety of disorders, including epilepsy (Luhmann et al, 1998;Chevassus-au-Louis et al, 1999;Jacobs et al, 1999a;Jacobs and Prince, 2005) and developmental dyslexia (Humphreys et al, 1991;Fitch et al, 1994Fitch et al, , 1997aHerman et al, 1997;Rosen et al, 1999;Peiffer et al, 2004).…”
mentioning
confidence: 99%